Redox Homeostasis and Immune Alterations in Coronavirus Disease-19 - Francesco Bellanti; Aurelio Lo Buglio; Gianluigi Vendemiale (Biology, 2022)
The global Coronavirus Disease 2019 (COVID-19) pandemic is characterized by a wide variety of clinical features, from no or moderate symptoms to severe illness. COVID-19 is caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) that first affects the respiratory tract. Other than being limited to lungs, SARS-CoV-2 may lead to a multisystem disease that can even be durable (long COVID). The clinical spectrum of COVID-19 depends on variability in the immune regulation. Indeed, disease progression is consequent to failure in the immune regulation, characterized by an intensification of the pro-inflammatory response. Disturbance of systemic and organ-related redox balance may be a further mechanism underlying variability in COVID-19 severity. Other than being determinant for SARS-CoV-2 entry and fusion to the host cell, reactive species and redox signaling are deeply involved in the immune response. This review sums up the present knowledge on the role of redox balance in the regulation of susceptibility to SARS-CoV-2 infection and related immune response, debating the effectiveness of antioxidant compounds in the management of COVID-19.